Dietary supplement intake by recreationally trained men and motives behind these procedures - Anna Maria Kurylas; Anna Kwiatkowska-Pamuła; Dorota Gniza (Kazimierz Wielki University, 2017)
Introduction: In the last 2-3 decades a significant increase in consumption of dietary supplements in physically active subjects has been observed. Supplements are easily accessible as they are sold by numerous companies on-line or at most food markets and pharmacies. Physically active men and women are constantly adding new supplements to their diets. Most scientists agree that exercise performance can be improved only through a combination of a proper training program, a well-balanced diet and specific supplementation geared to individual needs. Objective: The main objective of this research was to assess the type of supplements used by recreationally trained men in fitness clubs. Additionally the motives behind using particular supplements were evaluated. Material and methods: The research was conducted through interviews directly at fitness clubs and through the internet. The research subjects include 99 men between the age of 20 and 40 training at fitness clubs on a regular basis. The statistical analysis was conducted with the Statistica Microsoft Office Excel 2013 program. Results: From the 99 interviewed subjects 79% used supplements, with 47% declaring the objective of enhanced performance. Complex vitamin-mineral products were the most popular supplements among the interviewed group. The second most often used supplements included protein powders (52%), as well as protein-carbohydrate complexes and carbohydrate powders or liquids. According to the interviewed men creatine monohydrate was the most effective single supplement (25%). Conclusions: The most often reported motive for supplementation intake of recreationally trained men included enhanced performance and supplementation of daily diet. Taking into consideration the very dynamic development of dietary supplements industry such research should be conducted on a regular basis in different populations of men and women at a wide age scope.